Devices for ex vivo heart and lung perfusion. (4th March 2018) - Schraufnagel, Dean P.; Steffen, Robert J.; Vargo, Patrick R.; Attia, Tamer; Elgharably, Haytham; Hasan, Saad M.; Bribriesco, Alejandro; Wierup, Per
ABSTRACT: Introduction : The number of organs available for heart and lung transplantation is far short of the number that is needed to meet demand. Perfusion and ventilation of donor organs after procurement has led to exciting advances in the field of cardiothoracic transplantation. The clinical implications of this technology allows for techniques to evaluate the quality of an organ, active rehabilitation of organs after procurement and prior to implantation, and increased time between organ procurement and implantation. This ex-vivo perfusion technique has also been referred to in the lay press as the 'heart in a box' or 'lung in a box.' Areas covered : This review includes information from case reports, case series, and clinical trials on ex vivo heart and lung perfusion. The focus is on the devices, ventilation and perfusion techniques, outcomes, and application of the technology. Expert commentary : Ex vivo perfusion of donor hearts and lungs prior to transplantation has proven to be a viable alternative to standard cold-preservation strategies. Its use has allowed for ongoing expansion of the donor pool. The biggest barriers to expansion of this technology are access, cost, and lack of evidence which clearly supports superior outcomes.